Thermoviscoelasticity theory in the dynamic models of thermal shock - E. M. Kartashov; I. A. Nagaeva (Тонкие химические технологии)
While researching the thermal reaction of viscoelastic bodies under heatstroke conditions, the quasi-static HiltonLee-Sternberg theory of viscoelastic analogy generalization to dynamic models given inertial effects in the equations of motion was considered. The thermal reaction to heatstroke of a massive body (area with internal spherical cavity) with a sudden increase of its surface from initial To to Tc > 0 was researched. Numerical experiments were done, which revealed the qualitative difference of modeling results for the elastic body and viscoelastic body from rheological Maxwell and Kelvin models. It was found that the sudden heat of the surface of the viscoelastic body due to inertia force results in short-time stress close enough to the stress of the elastic, medium. Moreover, the difference of these stresses is decreased with increasing viscosity. The addition to this duration of action of inertial effects is about microseconds. During this time stress reaches its thermoelastic value before the growth of significant viscous flow. The qualitative behavior difference of viscoelastic Maxwell and Kelvin mediums on the body surface under conditions of sudden cooling within the quasi-static model of thermoviscoelasticity was described. The beginning of viscous flow in Maxwell medium which results in continuous stress decrease after discontinuous change tending to elastic medium stress was shown. On the contrary, in Kelvin medium jump of stress exceeds the value for the elastic medium, to which these stresses are tending.